2021
DOI: 10.1097/01.asw.0000722744.20511.71
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Economic Impact of Wound Care Using a Polyurethane Foam Multilayer Dressing

Abstract: OBJECTIVE To study the impact of a newly introduced dressing on efficiency and quality of care in routine clinical practice in a Spanish community setting. DESIGN AND SETTING An ambispective multicenter observational study was conducted in 24 primary care centers and 6 nursing homes in 4 different Spanish regions. The study was carried out between November 2017 and March 2019. PATIENTS AND INTERVENTION A total of 128 wounds in 94 patients (pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 17 publications
(15 reference statements)
0
11
0
1
Order By: Relevance
“…Accelerating wound healing can be interpreted as reducing society's financial expenditure, as it can reduce the likelihood of incapacity. Simultaneously, it also cuts costs by declining the frequency of dressing changes ( 52 ). A previous study demonstrated adding a collagen-containing dressing for treatment DFU management could reduce cost by 22% (from £2,897 to £2,255 per patient) compared with standard care alone ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accelerating wound healing can be interpreted as reducing society's financial expenditure, as it can reduce the likelihood of incapacity. Simultaneously, it also cuts costs by declining the frequency of dressing changes ( 52 ). A previous study demonstrated adding a collagen-containing dressing for treatment DFU management could reduce cost by 22% (from £2,897 to £2,255 per patient) compared with standard care alone ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Wound management costs include supplies and dressings (15%‐20%), nursing time (30%‐35%), and hospitalisation (more than 50%) 5‐7 . Frequent dressing changes increase the cost of wound care.…”
Section: Introductionmentioning
confidence: 99%
“…Wound management costs include supplies and dressings (15%‐20%), nursing time (30%‐35%), and hospitalisation (more than 50%). 5 , 6 , 7 Frequent dressing changes increase the cost of wound care. Therefore, use of dressings that reduce the need for cleansing and debridement of wounds and are clinically more effective, are of a priority.…”
Section: Introductionmentioning
confidence: 99%
“…29 Also, the use of PU foams led to reduced frequency of dressing changes and improved healing. 30 An example of early stage work using PU foams as wound dressings included incorporation of antimicrobial agents such as silver 31 or boric acid particles. 32 Here, we show, for the first time, how a branched polymer can become immobilized during the network forming and foam blowing process to form a stable S-IPN foam material.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Hydrophilic PUFs offer some advantages including retention of extrudate . Also, the use of PU foams led to reduced frequency of dressing changes and improved healing . An example of early stage work using PU foams as wound dressings included incorporation of antimicrobial agents such as silver or boric acid particles …”
Section: Introductionmentioning
confidence: 99%